Mitos Maung Putih Dalam Karya Lukis Modern - Fauzih, Vebriyan Tri; Pahala, Agam Akbar (Program Studi Pendidikan Seni Rupa FBS UNJ, 2023)
This creation aims to convey information about the influence of the Maung Putih myth in relation to ecological preservation and its correlation in maintaining the stability of nature which is visualized in the form of paintings. The weakening of myths as a control of people's behavior makes many people careless in using and exploiting natural resources which results in disrupted natural ecology. This creation departs from internal factors regarding the archetypal story with the late father which then refers to the conceptual, visual and operational aspects as well as several theoretical frameworks for creation with the aesthetic principles of modern art. This creation uses a qualitative method with an artistic research approach, where research and the practice of creating works are carried out simultaneously. Consists of the design of the method of creation, techniques and instruments of data collection, and techniques of data presentation and analysis. The creation of this work visualizes the presence of the white maung myth in preserving natural ecology by using pragmatic artistic interest, semi-figurative interest in forms, and modern aesthetic principles. The work is visualized in the form of a painting. The main tools and materials used are acrylic paint and spray paint on multiplex using a blending technique. The creation of this work is expected to serve as an appeal to the public to care for and always maintain and respect traditional culture in preserving natural ecology.